Outcomes of Early Versus Delayed Surgical Intervention in Long Bone Fractures - Khawand Bakhsh, M Aslam Mengal, Muhammad Tariq Hasani (Pakistan Journal of Medical & Health Sciences, 2023)
Background: To compare the functional outcomes, complication rates, and hospital stay between patients undergoing early versus delayed surgical intervention for long bone fractures. Methods: This comparative observational study was conducted at the Department of Orthopaedics, Bolan Medical Complex Hospital, Quetta, from May 2022 to August 2023. Sixty patients with acute fractures of the femur, tibia/fibula, humerus, or radius/ulna were enrolled and divided into two equal groups: early surgery (<48 hours from injury) and delayed surgery (≥48 hours). Demographic, injury-related, and perioperative data were recorded. Primary outcomes included time to union, functional scores at 6 months, and complication rates. Statistical analysis was performed using SPSS version 26, with a p-value <0.05 considered significant. Results: The mean time to union was significantly shorter in the early group compared to the delayed group (16.8 ± 3.5 vs. 19.4 ± 4.2 weeks, p = 0.007). Functional scores at 6 months were higher in the early group (85.6 ± 6.8 vs. 80.2 ± 7.1, p = 0.002). Hospital stay was reduced in the early group (6.2 ± 1.8 days vs. 8.5 ± 2.3 days, p < 0.001). Deep infections occurred only in the delayed group. Conclusion: Early surgical fixation within 48 hours yields superior functional recovery, faster union, and shorter hospitalization, with a trend toward lower complication rates. Adoption of early intervention protocols may improve patient outcomes, though individualized clinical assessment remains essential. Keywords: Long bone fracture, early fixation, delayed surgery, functional outcomes, fracture union, orthopaedic trauma.